Dynamic response of the saturated soil–reinforced concrete pile–superstructure interaction under repeated shaking. Issue 145 (June 2021) - Hayashi, Kazuhiro; Takahashi, Shuhei; Saito, Taiki
Abstract: This study conducted a shaking table test using a centrifuge model to clarify the dynamic response of the saturated soil–reinforced concrete pile–superstructure interaction under conditions of multiple earthquakes. The shaking table test was conducted under a 50-G field with multiple shaking inputs reproducing the mainshock and aftershocks to explore the interactions in terms of differences in relative soil density. The centrifuge test demonstrated the liquefaction of saturated soil during the mainshock and the simultaneous formation of plastic hinges at the pile head and base. However, the gradual compaction of the ground by repeated shaking did not promote the occurrence of liquefaction. Ground compaction caused the shear span ratio of the pile member to decrease and the inertial force acting on the superstructure to increase. It is possible that in the case of low relative soil density, the maximum inertial force during aftershock excitation exceeded that of mainshock excitation. Highlights: Experimental study of pile damage behavior during the soil liquefaction. The centrifugal shaking table test was conducted with multiple input waves. Gradual compaction occurred at the saturated sandy ground due to repeated shaking. Ground compaction caused the inertial force acting on superstructure to increase.